E-Business Impacts On Wholesale Market In China: Study On Auto Parts Market - Chen, Guang Ming (2005)
The author would like to seek some relationship and advantages of using E-Business to explore general extent of the impact of E-business towards China auto parts wholesale markets, investigate offline and online strategies and how wholesale companies exploit synergies from the coordination of electronic and physical channel.